The impact of meaningful activity : an investigation of the personal experiences of users of a mental health activity centre : a thesis presented in partial fulfilment of the requirements for a degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Harvey, Theresa (Massey University, 2018)
Activity centres are one way that those experiencing a severe and enduring mental illness can spend their time. Whilst there has been some research into meaningful activity internationally, within the New Zealand context there has been relatively little, particularly with this population group. This qualitative study took an Interpretative Phenomenological approach and sought to investigate participant’s experiences of one such activity centre. A sample of five participants who used the centre as part of their weekly schedule provided information via semi-structured interviews. From this data a set of five themes emerged; Belonging, Self-efficacy, Identity, Empowerment and Support, these being the key overall factors defining their time with the service. The participants illustrated their experiences with examples that personalised the journey of each. These examples became the sub-ordinate themes of the research and detailed the particular facets of the service and experiences that promoted their engagement and recovery. These included: Socialisation and relationships, Resources and outcomes of classes, Independence, Staff, Enjoyment and fun, Non-judgemental staff/ peers/environment, Flexibility & choice, A sense of a journey, Skill building, Personal growth, and Responsibility. These subthemes interacted with a high level of complexity with the themes and across the participants. This highlighted that each participant had a uniquely individual experience at the service. These individualised experiences support research which has been conducted around the concept of recovery in mental health where recovery emerges as an individual experience and journey. Overall experiences of the service were positive and participants reported that the service had been a positive factor in their recent lives and, for some, in the long term. This study was also found to support previous research which found that activity centres have the potential to improve life quality for vulnerable populations.
Keywords: Community mental health services -- New Zealand; Mentally ill -- Care -- New Zealand -- Case studies; Mentally ill -- Rehabilitation -- New Zealand -- Case studies